1985
DOI: 10.1212/wnl.35.5.752
|View full text |Cite
|
Sign up to set email alerts
|

Praziquantel in the treatment of neurocysticercosis

Abstract: Thirty-five patients with active neurocysticercosis were treated with praziquantel and followed for 1 year after therapy. CT and CSF analysis showed that 91% of patients with parenchymal cysts improved, and 47% of patients with chronic arachnoiditis had remission. A single treatment with praziquantel for 2 weeks, administered in a daily dose of 50 mg/kg of body weight, was highly effective in parenchymal cysticercosis but less effective in meningeal cysticercosis. The benefits were sustained for at least 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
5

Year Published

1985
1985
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 0 publications
2
31
0
5
Order By: Relevance
“…The prognosis of neurocysticercosis has improved re markably since the advent of praziquantel in 1978 [20,21]. The neurological symptoms became worse transiently in our patient after initiation of therapy, as it has been reported in other cases [I I], This may be ameliorated with prednisone and mannitol.…”
Section: Case Reportsupporting
confidence: 67%
“…The prognosis of neurocysticercosis has improved re markably since the advent of praziquantel in 1978 [20,21]. The neurological symptoms became worse transiently in our patient after initiation of therapy, as it has been reported in other cases [I I], This may be ameliorated with prednisone and mannitol.…”
Section: Case Reportsupporting
confidence: 67%
“…The authors of several studies have shown that praziquantel destroys as much as 70% of parenchymal brain cysticerci after a 15-day course of treatment at daily doses of 50 mg/kg. 65,70 This initial regimen was arbitrarily chosen. Since that time, recommended doses of praziquantel have ranged from 10 to 100 mg/kg for periods of 3 to 21 days.…”
Section: Cysticidal Drugsmentioning
confidence: 99%
“…This pioneer report was followed by a number of case series and controlled studies (using historical controls) showing the effi cacy of the drug (Botero and Castaño 1982 ;Sotelo et al 1984Sotelo et al , 1985SpinaFrança et al 1982 ). Such results prompted clinicians to widely use praziquantel in different forms of the disease.…”
Section: Trials Of Cysticidal Drugsmentioning
confidence: 99%